POSTGRADUATE MEDICAL EDUCATION: THE EXPERIENCE OF GREAT BRITAIN - Lysenko, О. (Continuing Professional Education: Theory and Practice, 2023)
This article represented the historical aspects of the doctors’ postgraduate training formation and restructuring in the United Kingdom, launched in 1970 by standardizing postgraduate training programs in medical schools and postgraduate education deaneries creation; the practice of establishing the specialized Post graduate medical education training board at the Department of Health of the United Kingdom described as a central coordinating body for postgraduate training and further association with the General Medical Council; stages of medical postgraduate training presented, including training two years of internship and 3-6 years of residency for further specialization (duration varies depending on the chosen speciality). Also the procedure of admission to postgraduate medical schools described. Procedure of accounting and control of future doctors professional achievements presented as a practise of personal port-folio creation, which consists of the following sections as the plan for personal and professional development; achievements in learning and their performance; report on mastering the skills required to implement clinical manipulation; feedback from colleagues about the ability to work in a team; descriptions independent examination of patients; the results of intermediate and final certification (in particular, the decision to issue the diploma on completion of internship). The organizational aspects of postgraduate medical education noted, particularly described the structure of postgraduate medical schools like the complex entities, which include: medical school, postgraduate dean’s offices and hospitals (total in the United Kingdom there are 19 schools of postgraduate medical education, of which 12 are located in England, 1- in Northern Ireland, 1 - in Wales and 5 in Scotland).